AMELIORASI BAHASA SASAK PADA MASYARAKAT TUTUR DI DESA SENGKERANG, PRAYA TIMUR: KAJIAN SOSIOLINGUISTIK - Khairil Anwar; Syahdan Syahdan; Muhammad Fadjri (Center of Language and Cultural Studies, 2019)
This study attempts to see amelioration form and its meaning Sasak language spoken in Sengkerang village and explores the reasons for using in a speech community. This study employed a qualitative descriptive method. Data were collected using observation and interview. Records using audio-visual aids were used to administer the observation and interview. Prior to analysis, records were transcribed verbatim to see their categories and classifications. Data were analyzed using theories proposed by Allan Keith and Keith Burridge, the steps of which included: reduction, data presentation, and conclusion. Results show that there are eleven forms of amelioration in Sengkerang village, namely 1) figurative, 2) flippancy, 3) remodeling, 4) circumcision, 5) clipping, 6) acronym, 7) abbreviation, 8) jargon, 9) hypernym, 10) hyponym, and 11) hyperbole. Meaning of the amelioration form is attached which it is spoken based on the context of which the speech is produced by a speaker. In addition, factors affecting to use the amelioration include humanity, physiological, characteristic, religiosity, and humor.